THEORETICAL ASPECTS AND EUROPEAN EXPERIENCE OF FORMATION AND DEVELOPMENT OF PROFESSIONAL COMPETENCES OF PUBLIC SERVANTS - Lakhyzha, Mykola; Kachan, Yana; Kulchii, Inna (Public Management and Policy, 2026)
The relevance of the study is determined by Ukraine’s need to study and implement the best European experience of reforms in education and science, as well as to modernize approaches to the professional training of public servants in the context of European integration, large-scale digitalization, and global challenges of 2025. The purpose of the article is to generalize theoretical approaches and analyze European practices in order to develop recommendations for improving the system of professional training and development of public servants in Ukraine. The article analyzes European experience in applying the competency-based approach to the training, retraining, and advanced professional development of civil servants on the basis of official sources and scientific research. A theoretical generalization and applied analysis of the transformation of professional competency formation systems is conducted, defining competency as a dynamic combination of knowledge, skills, ways of thinking, and moral and ethical values. The historical evolution of the competency-based approach is traced from its origins in the USA and Great Britain in the 1970s–1980s to its institutionalization in Ukraine through the Bologna Process and the laws “On Higher Education” and “On Civil Service.” Particular attention is paid to the German experience, characterized by high practicality and structural clarity. The four-level hierarchy of the German public service, educational requirements, and features of professional training are analyzed, including the role of dual education combining university study with practical training in public institutions. The activities of the Federal Academy of Public Administration and the Digital Academy are examined in the context of lifelong learning and modernization programs. The content of modern bachelor’s, master’s, and PhD programs in public management, administrative informatics, and digital transformation is described. Based on European practice, recommendations for improving educational programs in Ukrainian higher education institutions are proposed. The scientific novelty lies in the systematization of training methods for public servants with an emphasis on digital literacy and leadership development. The practical significance consists in the possibility of implementing German approaches to individualized and differentiated professional development. It is concluded that the competency-based approach is a strategic tool for ensuring institutional resilience, that modern public servants require both legal knowledge and soft skills, and that universities increasingly focus on developing critical thinking and practical application of knowledge.